Designing cooperative gamification: Conceptualization and prototypical implementation - Morschheuser, Benedikt; Maedche, Alexander; Walter, Dominic (Proceedings of the 2017 ACM Conference on Computer Supported Cooperative Work and Social Computing, 2017)
Organizations deploy gamification in CSCW systems to enhance motivation and behavioral outcomes of users. However, gamification approaches often cause competition between users, which might be inappropriate for working environments that seek cooperation. Drawing on the social interdependence theory, this paper provides a classification for gamification features and insights about the design of cooperative gamification. Using the example of an innova-tion community of a German engineering company, we present the design of a cooperative gamification approach and results from a first experimental evaluation. The findings indicate that the developed gamification approach has positive effects on perceived enjoyment and the intention towards knowledge sharing in the considered innovation community. Besides our conceptual contribu-tion, our findings suggest that cooperative gamification may be beneficial for cooperative working environments and represents a promising field for future research.
CRIS-Team Scopus Importer:2021-02-01
Keywords: Collaboration; Cooperation; CSCW systems; Design research; Experiment; Gamification; Innovation community